Proposed Knowledge Management for Business Development at Relife Property Management - Sabila Syarafina; Dedy Sushandoyo (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
The pandemic has affected various business sectors, including the property management industry. Restrictions on movement and gatherings of people have caused some difficulties, especially in the events, travel and tourism industries. Relife Property Management is one of the companies impacted a lot by the pandemic because their business is related to these industries. In this uncertain world of business, the only sure source of lasting competitive advantage is knowledge. Therefore, activities of managing knowledge in this company are analyzed. With knowledge management (KM), businesses will not only survive the pandemic, but develop. The purpose of this study is to identify practices that have been carried out by companies in managing their knowledge, identify KM programs that are suitable in the digital era and propose plans for implementing KM system and programs for the company’s business development. This research was conducted using qualitative methods with primary data collected with observations and interviews, and secondary data from documents and reports. The results of this study indicate that the company has already been practicing activities related to managing their knowledge, but they have not implemented a well-structured KM system, and their activities are not based on KM theory. Therefore, KM system and programs are designed and proposed based on theories such as the SECI and PPT models for the company’s business development. The proposed business solution consists of a diagram with a goal orientation, the formulation of a KM model, a proposed KM conversion mechanism, and a KM roadmap. The implementation plan for the company is also proposed in this study.